2015
DOI: 10.1002/2014wr016487
|View full text |Cite
|
Sign up to set email alerts
|

An efficient and guaranteed stable numerical method for continuous modeling of infiltration and redistribution with a shallow dynamic water table

Abstract: We have developed a one-dimensional numerical method to simulate infiltration and redistribution in the presence of a shallow dynamic water table. This method builds upon the Green-Ampt infiltration with Redistribution (GAR) model and incorporates features from the Talbot-Ogden (T-O) infiltration and redistribution method in a discretized moisture content domain. The redistribution scheme is more physically meaningful than the capillary weighted redistribution scheme in the T-O method. Groundwater dynamics are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 27 publications
0
20
0
Order By: Relevance
“…Water infiltration occurs in both the VPFPs and the soil matrix but water in the VPFPs reaches the sub‐layer bottom very quickly and goes below the preferential flow layer to become groundwater recharge. In the matrix domain, downward water movement was simulated using the GARTO method [ Lai et al ., ]. Water from the VPFP domain was assumed to not interact with the matrix, and LPFPs and VPFPs were treated as disconnected.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Water infiltration occurs in both the VPFPs and the soil matrix but water in the VPFPs reaches the sub‐layer bottom very quickly and goes below the preferential flow layer to become groundwater recharge. In the matrix domain, downward water movement was simulated using the GARTO method [ Lai et al ., ]. Water from the VPFP domain was assumed to not interact with the matrix, and LPFPs and VPFPs were treated as disconnected.…”
Section: Methodsmentioning
confidence: 97%
“…This structure assumed that Darcian matrix flow is the only type of flow in the unsaturated zone. We used the GARTO scheme [ Lai et al ., ] to simulate soil matrix flow. The GARTO scheme agrees closely with the numerical solution of Richards' equation [ Richards , ] but is much more computationally efficient with guaranteed convergence and mass conservation.…”
Section: Methodsmentioning
confidence: 99%
“…The sublayer was further divided into two domains, a matrix infiltration domain and a vertical PFP domain. In the matrix infiltration domain, downward water movement was simulated using the Green‐Ampt infiltration with redistribution (GAR) model with features from the Talbot‐Ogden (T‐O) infiltration and redistribution method (Lai et al, ), which is a simplified version of the finite moisture content solution of the Soil Moisture Velocity Equation (Ogden et al, , ). Macropores in the vertical PFP domain were assumed to fully penetrate the preferential flow layer and were referred to as “effective percolating vertical PFPs.” Water movement through these effective percolating vertical macropores was explicitly simulated using a laminar pipe flow equation.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, Lai et al [2015] found that only 10 groundwater bins allowed accurate simulation of the effects of water table dynamics on a Green and Ampt redistribution (GAR) scheme [Ogden and Saghafian, 1997].…”
Section: Groundwater Table Dynamics Effects On Vadose Zone Water Contentmentioning
confidence: 99%